Anti‐adipogenic β‐sitosterol and lupeol from Moringa oleifera suppress adipocyte differentiation through regulation of cell cycle progression. Issue 8 (11th April 2022) - Vasanth, Karunamoorthy; Minakshi, Guha Chowdhury; Velu, Karthick; Priya, Tanu; Kumar, R. Mohan; Kaliappan, Ilango; Dubey, Govind Prasad
Abstract: Triterpenes and phytosterols enriched herbal formulations are known for glucose regulation and lipid metabolism. In this study, triterpenes and phytosterols from Moringa oleifera stem bark have been tested for their role in adipocyte differentiation. Chromatographic analysis revealed a wide range of phenolics, highlighting the presence of flavonoids (kaempferol, quercetin, and rutin), terpenoids (lupeol), and phytosterol (stigmasterol, β‐sitosterol). Lupeol and β‐sitosterol reduced cell viability in a dose‐dependent manner showcasing increased G1 phase cell accumulation while reducing other cell cycle phases (S and G2 /M) and significant lowering of intracellular lipid accumulation. Additionally, lupeol (35.37% at 32 μM) and β‐sitosterol (42.97% at 16 μM) inhibited reactive oxygen species generation and increased glucose uptake in adipocytes. Collectively, our results indicate that lupeol and β‐sitosterol efficaciously attenuated adipogenesis via a controlled cell cycle progression and enhanced glucose uptake in adipocytes. Practical applications: Active components of Moringa oleifera effectively regulate adipocyte differentation suggest that it can be good medicial supllement for control of obesity. Abstract : Triterpenes and phytosterols have been extracted and separated from Moringa oleifera stem bark. Dose‐dependent reduction of cell viability found when lupeol and β – sitosterol administered and showcasing increased G1 phase cell accumulation while reducing other cell cycle phases (S and G2/M) and significant lowering of intracellular lipid accumulation.